Posthepatectomy liver failure: a definition and grading by the International Study Group of Liver Surgery (ISGLS) - Rahbari, Nuh Nabi; Garden, O. James; Padbury, Robert; Brooke-Smith, Mark; Crawford, Michael; Adam, Rene; Koch, Moritz; Makuuchi, Masatoshi; Dematteo, Ronald P.; Christophi, Christopher; Banting, Simon; Usatoff, Val; et al. (Surgery, 2011)
Background - Posthepatectomy liver failure is a feared complication after hepatic resection and a major cause of perioperative mortality. There is currently no standardized definition of posthepatectomy liver failure that allows valid comparison of results from different studies and institutions. The aim of the current article was to propose a definition and grading of severity of posthepatectomy liver failure. - Methods - A literature search on posthepatectomy liver failure after hepatic resection was conducted. Based on the normal course of biochemical liver function tests after hepatic resection, a simple and easily applicable definition of posthepatectomy liver failure was developed by the International Study Group of Liver Surgery. Furthermore, a grading of severity is proposed based on the impact on patients' clinical management. - Results - No uniform definition of posthepatectomy liver failure has been established in the literature addressing hepatic surgery. Considering the normal postoperative course of serum bilirubin concentration and International Normalized Ratio, we propose defining posthepatectomy liver failure as the impaired ability of the liver to maintain its synthetic, excretory, and detoxifying functions, which are characterized by an increased international normalized ratio and concomitant hyperbilirubinemia (according to the normal limits of the local laboratory) on or after postoperative day 5. The severity of posthepatectomy liver failure should be graded based on its impact on clinical management. Grade A posthepatectomy liver failure requires no change of the patient's clinical management. The clinical management of patients with grade B posthepatectomy liver failure deviates from the regular course but does not require invasive therapy. The need for invasive treatment defines grade C posthepatectomy liver failure. - Conclusion - The current definition of posthepatectomy liver failure is simple and easily applicable in clinical routine. This definition can be used in future studies to allow objective and accurate comparisons of operative interventions in the field of hepatic surgery.